2009
DOI: 10.2147/copd.s4862
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frequency of COPD exacerbations on pulmonary function, health status and clinical outcomes

Abstract: Background: COPD exacerbations are responsible for the morbidity and mortality of this disease. The relationship between exacerbations and patient-related clinical outcomes is not clearly understood. Methods: A retrospective analysis of two 1-year, placebo-controlled clinical trials with tiotropium 18 µg daily was conducted to examine relationships between exacerbations and other clinical outcomes. The relationship between FEV 1 , St. George's Respiratory Questionnaire (SGRQ), and the transition dyspnea index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 32 publications
(40 reference statements)
0
23
0
1
Order By: Relevance
“… 1 Affected patients suffer from frequent and recurrent exacerbations, which are defined by the Global Initiative for Chronic Obstructive Lung Disease (GOLD) as events in the course of COPD, characterized by acute changes in patients’ baseline dyspnea, cough, and/or sputum exceeding ordinary day-to-day variations and which may warrant changes to medication. 2 Accordingly, COPD exacerbations are associated with rapid decline in lung function and physical activity, increased risk of hospitalization and mortality, 3 , 4 deterioration in health-related quality of life (HRQoL), and substantial financial burden. 3 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Affected patients suffer from frequent and recurrent exacerbations, which are defined by the Global Initiative for Chronic Obstructive Lung Disease (GOLD) as events in the course of COPD, characterized by acute changes in patients’ baseline dyspnea, cough, and/or sputum exceeding ordinary day-to-day variations and which may warrant changes to medication. 2 Accordingly, COPD exacerbations are associated with rapid decline in lung function and physical activity, increased risk of hospitalization and mortality, 3 , 4 deterioration in health-related quality of life (HRQoL), and substantial financial burden. 3 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“… 2 Accordingly, COPD exacerbations are associated with rapid decline in lung function and physical activity, increased risk of hospitalization and mortality, 3 , 4 deterioration in health-related quality of life (HRQoL), and substantial financial burden. 3 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Previous research shows that the Chinese version of COPD-MSD (Ch-COPD-MSD) has good reliability and validity, which can help clinicians to assess patients with COPD morning symptoms in China. 15 Exacerbations of COPD directly affect the course of the disease, which is associated with a faster rate of lung function decline, 16 impaired health status, 16,17 and increased risk of mortality, 18,19 and is a vital indicator evaluation of the longterm risk of poor prognosis. 20 Thus, reducing the risk of exacerbations is a crucial goal of COPD therapy.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Despite the promising improvements in lung function demonstrated with current treatments, the question remains whether interventions that significantly improve FEV1 are also associated with improvements in other outcome measures. Several studies have demonstrated a significant relationship between poor lung function and a decline in health status in patients with COPD; [33][34][35][36][37][38] however, there is limited evidence that changes in lung function associated with a therapeutic intervention correlate with changes in patient-centred outcomes. In a recent analysis, pooled data from three indacaterol studies (12,26, and 52 weeks in duration) were used to examine relationships between change from baseline of FEV1 and clinical outcomes (dyspnoea (TDI score), health status (SGRQ score) and exacerbations).…”
Section: Laba/lama Combination Therapy and The Future Of Copd Managementmentioning
confidence: 99%